Prevalence and phylogenetic analysis of hepatitis E virus in pigs in Vietnam - Hu Suk Lee; Duy Tung Dao; Vuong Nghia Bui; Ngoc Anh Bui; Thanh Duy Le; Hung Nguyen-Viet; Grace, Delia; Thakur, K.K.; Hagiwara, K. (Springer, 2020)
Hepatitis E virus (HEV) is a zoonotic disease and has been reported around the world. The main objective of this study was to evaluate the sero-prevalence and phylogenetic analysis of HEV in Vietnam. Pig blood and fecal pooled samples were collected to assess the prevalence of HEV. We assessed the true prevalence (TP) of HEV from apparent prevalence (AP) by taking into account the sensitivity and specificity of diagnostic tests using a Bayesian approach. For phylogenetic analysis, the data compared with worldwide HEV reference strains including all eight genotypes (G1-G8) which were identified in previous study.A total of 475 sera and 250 fecal pooled samples were collected at slaughterhouses and pig farms from five provinces, in Viet Nam. Overall, the sero-AP of HEV was 58.53% (95% confidence interval: 53.95–62.70) while the sero-TP was slightly higher (65.43, 95% credible interval: 47.19–84.70). In terms of pooled samples, overall, the RNA-AP was 6.80% (95% confidence interval: 4.01–10.66). One strain in Hanoi, two strains in Dak Lak, seven strains in An Giang, four strains in Son La and two strains in Nghe An were isolated. The phylogenetic tree demonstrated that 19 Vietnamese strains were clustered into HEV 3 and 4.This study provided evidence that HEV is circulating in domestic pigs in Vietnam. From a public health perspective, it is very important to raise public awareness for high-risk groups (e.g. slaughterhouse workers, pig traders, farmers and market sellers) who have more opportunities to come in contact with pig and contaminated meats.